Anion-modulated nickel-based nanoheterostructures as high performance electrocatalysts for hydrogen evolution reaction. Issue 24 (10th June 2020) - Li, Yang; Gao, Yugan; Yang, Sen; Wu, Chengqi; Tan, Yiwei
Abstract : Ni-based anion-modulated nanoheterostructures are designed and fabricated as electrocatalysts for the hydrogen evolution reaction (HER). The modulation of interfacial anions is a unique option in exploiting excellent electrocatalysts. Abstract : The two-phase interface of hybrid catalysts plays an important role in improving their electrocatalytic activity due to the strong electronic interactions at the interface region. Therefore, we aim to elaborately design and exploit the architectures and interactions at the interface of binary nanoheterostructures, thus offering great potential to significantly boost the electrocatalytic performance of the hydrogen evolution reaction (HER) and gain deep insight into the HER mechanisms. Herein, we present a new strategy for the fabrication of a library of Ni-based anion-modulated nanoheterostructures (Ni-a-m-NHs), including nickel foam (NF)-supported ultrathin Ni3 Se4 nanosheets decorated with uniform Ni2 P nanoparticles, Ni3 S4 nanorods, and NiSe2 nanowires, as highly active electrocatalysts for the HER. All the Ni-a-m-NH catalysts exhibited superior electrocatalytic HER performances compared to that of their corresponding single-component catalysts and previously reported hybrid electrocatalysts. Unlike multi-metal hybrid electrocatalysts, Ni-a-m-NHs uniquely modulate the electronic interactions at the interface region due to the large difference in the electronegativity and magnitude of the electron-attracting effects between their different nonmetallic elements, which is supported by the experimental and DFT analyses.